Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyt.2021.797545
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of COVID-19 on Healthcare Workers in Saudi Arabia: A Year Later Into the Pandemic

Abstract: Objective: The COVID-19 pandemic poses unprecedented challenges to healthcare workers worldwide. This study sought to estimate the prevalence of depression, anxiety, and stress among healthcare workers in Saudi Arabia, and to identify the factors associated with these psychological disorders.Methods: A cross-sectional questionnaire-based study was conducted from January 21 to March 2, 2021. Physicians, pharmacists, nurses, and other healthcare workers from different parts of Saudi Arabia were recruited through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
5
16
3
Order By: Relevance
“… 30 Our study showed 16.94% of MLS have anxiety during the pandemic, which is similar to the findings of Chew et al who reported 15.7% anxiety among HCWs in a multinational study and, very much lower than the study by Giusti et al and Almalki et al that reported anxiety in 71.2% and 60.88% of health professionals, respectively. 16 , 31 , 32 The finding of this study is also in accordance to the study by Chen et al that records 18.1% anxiety among paediatric medical staff members. 33 This study also accounts for 25.91% of depressive symptoms among MLS, similar to a study carried out in China.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 30 Our study showed 16.94% of MLS have anxiety during the pandemic, which is similar to the findings of Chew et al who reported 15.7% anxiety among HCWs in a multinational study and, very much lower than the study by Giusti et al and Almalki et al that reported anxiety in 71.2% and 60.88% of health professionals, respectively. 16 , 31 , 32 The finding of this study is also in accordance to the study by Chen et al that records 18.1% anxiety among paediatric medical staff members. 33 This study also accounts for 25.91% of depressive symptoms among MLS, similar to a study carried out in China.…”
Section: Discussionsupporting
confidence: 92%
“… 13 Studies suggested that HCWs had the psychological symptoms of anxiety and depression due to the COVID-19 pandemic. 14 16 The literature on the health consequences of HCWs providing care to COVID-19 patients is increasing. However, the limited study is available on knowledge, practice and physiological impact of COVID-19 among MLSs.…”
Section: Introductionmentioning
confidence: 99%
“…In line with results from our previous study and that of other research during COVID-19, women and those with chronic illness were found to be significantly associated with higher severity of DAS (21, 39, 40). These results are consistent with evidence showing women and those with chronic illness to be more vulnerable to psychological problems than males and those without chronic illness (21, 41).…”
Section: Discussionsupporting
confidence: 92%
“…This study was one of the first in the Gulf Council Cooperation (GCC) region to conduct a cross-sectional survey on the prevalence and severity of psychological distress among HCWs in KSA during the COVID-19 pandemic. While several other studies have explored the psychological impact of COVID-19 on HCWs and the general public using different scales in KSA [ 39 41 ], our study looked at psychological distress in HCWs at the national level [ 39 , 42 ], included a larger sample taken from six major hospitals, and examined psychological distress in general rather than focusing on specific disorders [ 40 , 41 , 43 , 44 ]. Furthermore, while our results are in line with global findings, Saudi Arabia is culturally different in terms of its psychological landscape [ 45 ], and it is possible that religious and cultural beliefs impacted how HCWs responded to the survey.…”
Section: Discussionmentioning
confidence: 99%